Methodological Bases with Professional Terms in Non-Philological Directions of Universities (On the Example of Russian Language) - Rustamova Feruzakhon Makhmudzhanovna (Global Scientific Publishing, 2023)
This article examines the study of architectural and construction terms and terminology in the classroom of the Russian language in non-philological areas of universities. With the help of interactive methods, we work with professional terms (terminology).
Keywords: terms; terminology; Russian; methods